2009
DOI: 10.3748/wjg.15.570
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus extract inhibits destruction of gastric cancer cells to mesothelial cells by anti-apoptosis

Abstract: AIM:To determine the inhibitory effect of Astragalus memebranaceushas on gastric cancer cell supernatantinduced apoptosis of human peritoneal mesothelial cells. METHODS:Human peritoneal mesothelial cell (HPMC) line HMrSV5 was co-incubated with gastric cancer cell supernatant (MKN45) and/or Astragalus memebranaceushas. Morphological changes in gastric cancer cells were observed under phase-contrast microscope. Quantitative cell damage was determined by MTT assay. Apoptosis was determined under transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Mesothelial cells are the primary component of the peritoneum (27). Following adhesion onto peritoneal tissue, gastric cancer cells that have interacted with proteolytic enzymes may migrate into the ECM via mesothelial cells (28). The hydrolysis of the ECM by a malignant tumor is a necessity for tumor migration and invasion, which involves numerous proteolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Mesothelial cells are the primary component of the peritoneum (27). Following adhesion onto peritoneal tissue, gastric cancer cells that have interacted with proteolytic enzymes may migrate into the ECM via mesothelial cells (28). The hydrolysis of the ECM by a malignant tumor is a necessity for tumor migration and invasion, which involves numerous proteolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a variety of potential therapeutic roles of Astragalus have been demonstrated in the treatment of immunodeficiency syndromes and cancer (Anonymous, 2003). For instance, it has been reported that Astragalus extract inhibits destruction of gastric cancer cells to mesothelial cells through anti-apoptosis (Na et al, 2009). The active pharmacological constituents of Astragalus membranaceus contain various bioactive compounds, such as flavones, polysaccharides and saponins as well as L-arginine or L-canavanine (Ma et al, 2002b).…”
Section: Protective Effect Of Astragalus Polysaccharides On Liver Injmentioning
confidence: 99%
“…For example, astragalus membranaceus (AM) injection supplemented with chemotherapy was found to inhibit the development of tumor, decrease the toxic-adverse effect of chemotherapy, elevate the immune function of organism and improve the quality of life in patients of malignant tumor (McCulloch et al, 2006). Similar results were obtained in the study with gastric cancer (Na et al, 2009). Besides, it was reported that AM injection could enhance the anti-tumor metastasis action of dendritic cells, effectively promote the immune response of tumor-bearing host and therefore had obviously inhibitory effect on cancer metastasis in vivo (Dong et al, 2005).…”
Section: Xin-yan Huangmentioning
confidence: 53%